Typical Characteristics of Islamic Religious Education and Its Role in Fostering Islamic Character - Hildan Ramadhan; Hafidz; Ummu Izzatul Uswatun Khalisah; Lutfia Nazella Ulya; Julianda; Zahrina Wardah; Ma’ruf Ardiyanto (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
Islamic Religious Education has a very important role in the formation of Islamic character. This education offers a holistic approach that aims to create individuals who not only understand the teachings of the religion but are also able to apply them in various aspects of life. Thus, Islamic Religious Education has a strategic role in shaping Islamic character, especially in the challenging modern era. This research aims to identify the distinctive characteristics of PAI and explore its contribution in shaping individuals in accordance with Islamic values. The main problem raised is how the distinctive characteristics of PAI can be implemented effectively to create a balanced character between spiritual, moral, intellectual, and social aspects. The research method used is literature review and critical analysis of various relevant sources. The results of the study show that PAI is not only normative but also applicative, offering a holistic approach that emphasizes the understanding and application of Islamic values in daily life. This article also identifies key challenges in the implementation of PAI, such as the relevance of the curriculum to the needs of the era of globalization, as well as providing solutions based on an integrative and contextual approach. This study concludes that PAI plays an important role as an instrument for the formation of a generation with Islamic character, noble character, and firm faith, as well as being able to make a positive contribution to modern society.